Tumor blood flow from arterial spin labeling perfusion MRI: A key parameter in distinguishing high‐grade gliomas from primary cerebral lymphomas, and in predicting genetic biomarkers in high‐grade gliomas. Issue 4 (6th February 2013) - Yoo, Roh‐Eul; Choi, Seung Hong; Cho, Hye Rim; Kim, Tae Min; Lee, Se‐Hoon; Park, Chul‐Kee; Park, Sung‐Hye; Kim, Il Han; Yun, Tae Jin; Kim, Ji‐Hoon; Sohn, Chul‐Ho; Han, Moon Hee; et al.
Abstract : Purpose: To evaluate the usefulness of pseudo‐continuous arterial spin labeling (pCASL) imaging in differentiating high‐grade gliomas from lymphomas and in noninvasively predicting genetic biomarkers in high‐grade gliomas. Materials and Methods: Twelve glioblastoma multiforme (GBM), 3 anaplastic astrocytoma (AA), 5 recurred GBM, and 9 lymphoma patients underwent conventional MR and pCASL imaging. On pCASL perfusion map, mean absolute tumor blood flow (mTBF) was calculated from five regions of interest (ROIs) within the enhancing portion of the tumor. Relative TBF (rTBF = mTBF/mBFgm × 100) was also calculated. mTBF and rTBF of high‐grade gliomas and lymphomas were compared using unpaired Student's t‐test and receiver operating characteristic (ROC) analysis. Additionally, the association of TBF and six immunohistochemically confirmed genetic biomarkers was analyzed by Pearson correlation analysis in the group of high‐grade gliomas. Results: Both mTBF and rTBF of the high‐grade gliomas were significantly higher than those of the lymphomas: 92.1 ± 34.7 versus 53.6 ± 30.5 mL/min/100 mg ( P = 0.008) and 182.3 ± 69.5 versus 92.5 ± 44.9 ( P = 0.002), respectively. Only epidermal growth factor receptor (EGFR) expression status showed a significant positive correlation with mTBF( P = 0.015) and rTBF( P = 0.007). Conclusion: pCASL imaging may facilitate differentiation of high‐grade gliomas from lymphomas and prediction of EGFR expression status in high‐grade gliomas. J. Magn. Reson. Imaging 2013;38:852–860. © 2013 Wiley Periodicals, Inc.